Uji Efektivitas Pupuk Majemuk Npk Super + Humic Acid Terhadap Pertumbuhan dan Produktivitas Tanaman Kedelai - Tarbiyatul Munawwarah; Wawan Banu Prasetyo (Jurnal Riset Agribisnis dan Peternakan, 2018)
Fertilizer is a mandatory requirement in crop cultivation and its existence is needed to support and increase the availability of nutrients in agricultural land. Therefore new methods and fertilizer products are needed to be developed to meet these needs. Research on the use of NPK, humic acid, and compost in soybean farming has been carried out. The study was arranged in a Randomized Block Design with 6 treatments and 4 replications. The treatments consist of urea 75 kg / ha + SP36 75 kg / ha + KCl 100 kg / ha (N0), urea 75kg / ha + SP36 75 kg / ha + KCl 100kg / ha + straw compost 2 tons / ha (N1), NPK super 200kg / ha + Urea 100kg / ha (N2), NPK super 200kg / ha + urea 100kg / ha + straw compost 2ton / ha (N3), NPK super + humic acid 0,0075 (N4), NPK super + humic acid 0.015 (N5) ). Parameters observed: plant height, number of crop branches, and number of crop filled pods. The results showed the highest average height of plants was found in N2 treatment (76.75cm). In observing the results, the highest average weight of plant pods was found in the N5 treatment (131.67 g).